Analysis of analgesic, antipyretic, and nonsteroidal anti‐inflammatory drug use in pediatric prescriptions - Tânia R. Ferreira; Luciane C. Lopes (Brazilian Society of Pediatrics, 2016)
Objective: Data on clinical practice in pediatrics on the use of analgesic, antipyretic, and nonsteroidal anti‐inflammatory drugs (NSAIDs) considering the best available evidence and regulatory‐agency approved use are uncertain. This study aimed to determine the frequency of prescription of these drugs according to the best scientific evidence and use approved by regulatory agencies. Methods: This was a cross‐sectional study of 150 pediatric prescriptions containing analgesic, antipyretic, and NSAIDs, followed by interview with caregivers at 18 locations (nine private drugstores and nine Basic Health Units of the Brazilian Unified Health System). The assessed outcomes included recommended use or use with no contraindication, indications with benefit evidence, and health surveillance agency‐approved use. Data were analyzed in electronic databases and the variables were summarized by simple frequency. Results: A total of 164 analgesic, antipyretic, and NSAIDs were prescribed to 150 children aged 1 to 4 years (38.6%). Dipyrone was included in 82 (54.6%) and ibuprofen in 40 (26.6%) prescriptions. Non‐recommended uses were identified in 15% of prescriptions and contraindicated uses were observed in 13.3%. Nimesulide (1.5%) is still prescribed to children younger than 12 years. The dose was incorrect in 74.3% of prescriptions containing dipyrone. Of the 211 reported clinical indications, 56 (26.5%) had no evidence of benefit according to the best available scientific evidence and 66 (31.3%) had indications not approved by the regulatory agencies. Conclusion: There are significant discrepancies between clinical practice and recommended use of analgesic, antipyretic, and NSAIDs in pediatrics.